Studying The Role of Political Parties in The Implementation Of Democracy in Indonesia - Abdul Malik (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2020)
Political parties are an important element in democracy. There is no country with a democratic system without a political party. Political parties in Indonesia have gone through a long history since the Old Order to the current Reform Order. Political parties have functions, among others, as a means of political communication, a means of political socialization, a means of political recruitment, as a regulator of conflicts. The four functions of political parties have actually been running, but in reality many people are dissatisfied with the performance of political parties, causing public trust in political parties to decline. In the perspective of society, political parties are no more than an attempt to gain power, and after power is seized, the people are abandoned.